JURNALISME ADVOKASI DENGAN METODE JURNALISME CROWDSOURCING DAL AM BERITA KOLABORASI MEDIA DEDUKTIF DAN TIRTO - Ami Fatimatuz Zahro; Febria Adha Larasati (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2024)
This research aims to gain an in-depth understanding of how crowdsourcing can be used in investigative journalism practices by the Deductive News Media. It is important to answer the question why and how crowdsourcing may be utilized in investigatory journalistic practices. Research theory is based on the paradigm of qualitative research using case study methods. As for the subject of the research, it is a Deductive Reporter, while the object of its research is an in depth coverage related to reports about the challenges and threats faced by the Student Press Institute (LPM) in Indonesia during 2015-2022 entitled "Student Press is Still Vulnerable Upon Intimidation". The research population consisted of the Deductive Reporters involved in the coverage, while the sample was taken from that coverage during the specified time period. It is also supported by data collection techniques such as results of interviews, observations, as well as documentation in the field objectively. Moreover, data reduction is carried out continuously as long as the qualitative research continues until the final report is compiled. Through the research methods used, it is expected that this research will provide a deep understanding of investigative journalism practices using crowdsourcing and its impact on the coverage of journalistic news media Deduktif. Keywords: crowdsourcing, investigative journalism, student press, case studies, in depth coverage